Facts, trends and challenges in modern software development. (1st January 2012) - Maximilien, E. Michael; Campos, Pedro
The IT industry is not new to change and evolution, however, we are now in an era of two fundamental waves of IT changes. First, the post-PC era, where mobile devices and tablet-like devices are giving end-users the ability to consume information when they want it and where they want it. Second, the post-server era where companies no longer need to neither buy nor provision servers in their own data centres but instead rent the compute resources as needed. This twin change has direct consequences to how end-users consume software, how that software is produced, and how it is delivered.